Manfaat Asuransi Usahatani Padi dalam Menanggulangi Risiko Kerusakan Akibat Hama Penyakit (Studi Kasus pada Subak Sangeh, Desa Sangeh, Kecamatan Abiansemal, Kabupaten Badung, Provinsi Bali) - NI KADEK MARITA DEWI; KETUT BUDI SUSRUSA; IDA AYU LISTIA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Benefits of Insurance of Rice Insurance in Eradication of Damage Risk Because of Diseases (Case Study in Sangeh Subak, Sangeh Village, Abiansemal District,Regency of Badung, Bali Province) The rat attack that occurred in July 2017 resulted in 8.96 ha of land in Subak Sangeh experiencing crop failure so farmers get a claim of Rp 53,760,000. The granting of this claim is intended to enable farmers to cover losses due to damage to the previous planting season and to have the capital of farming in the next planting season. Based on that it is interesting to do research on the benefits of rice farm insurance in tackling the risk of damage caused by pest disease in Subak Sangeh, as well as farmers response to the program.Farmers' responses were analyzed qualitatively with attitude approach based on percentage of average score obtained through structured interviews using questionnaires. While the benefits of rice farm insurance are analyzed quantitatively based on the ratio of claims fund to production cost.The result of comparison of claim fund with production cost of Subak Sangeh in one planting season is 121,54% or morethan 100%, meaning rice farm insurance has benefit in tackling damage caused by pest, farmers response is positive, seen from the attitude of farmers in general agreed to the socialization and implementation of the program.